PERSEPSI SISWA TENTANG PERILAKU SEKSUAL REMAJA DAN IMPLIKASINYA TERHADAP PELAYANAN BIMBINGAN DAN KONSELING - fitria, aida; ., Daharnis (Konselor, 2013)
The background of the research was based on pre observation about negative sexuality behavior in one city of West Sumatera. Sexual behavior is negatively related to the alleged wrong perception of sex. From the result, authors are interested in conducting research on student’s perceptions of teenager sexual behavior and its implications for guidance and counseling services. Its population is SMPN student’s in one of the city of West Sumatra in class VII, VIII, and IX of the school year 2012/2013 as many as 445 student’s. The sampling technique is stratified random sampling with a sample of 112 student’s. Research instrument was a questionnaire of student’s perceptions of teenager sexual behavior. The data obtained were analyzed by using percentages. From this research, the overall perception of student’s is really about sexual behavior was categorized as very positive.